Beauty Tech Nails: towards interaction and functionality - Araujo, Ada; Vega, Katia; Castro, Thais; Gadelha, Bruno (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
There has been a significant increase in the use of mobile devices and their possibilities for interaction. Currently several actions in people’s surrounds, both face-to-face and in virtual spaces can be performed by using these devices. Some examples are the control of some home appliances, location sharing and facial, voice and gesture recognition without direct contact. Based on that, Beauty Technology proposes an interaction approach embedded in beauty products, so that the user can interact with the world in a discreet and comfortable way. In this context, we present, in this article, an exploratory study on the utilities and limitations of beauty tech nails for remote interaction actions on mobile devices.